Customer Experience: Analysis of Creativepreneur Differentiation Strategies in The Development of Local Culinary Services - Geitsa Zahira Sofa; Vina Nur Oktaviani; Ardi Setyo Anggoro; Alvin Naufal Fernanda; Senny Luckyardi; Eddy Soeryanto Soegoto (IJSM, 2026)
This study aims to explore the differentiation strategies employed by creative entrepreneurs in improving customer experience in the domestic culinary service industry, with Makaroni Ngehe as a case. The research process utilizes the qualitative descriptive methodology by employing observation, in-depth interviews, and documentation studies on customers who have been selected with the purposive sampling method. The results show that sensory features (colour, aroma, touch, flavour), quality of packaging of the product, and ease of availability online all play an important role in creating positive consumer perceptions. The SWOT analysis shows that strengths are product quality and loyalty of customers, and weaknesses are product shelf life after opening and lack of interest among consumers in nutrition facts. Brief discussion confirms that customer experience-based differentiation strategies have the potential to create a strong brand identity, increase competitiveness, and keep up with changing local food trends. The result of this study reveals that Makaroni Ngehe has managed to apply creativity, innovation, and consumer behavior knowledge in maintaining its business existence. The contribution of this study is expected to be practically and theoretically significant in establishing innovative marketing strategies and improving the competitiveness of Indonesian culinary MSMEs.